Measurements of tt¯ cross sections in association with b jets and inclusive jets and their ratio using dilepton final states in pp collisions at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Elsevier BV, 2018)
The cross sections for the production of tt¯bb¯ and tt¯jj events and their ratio σtt¯bb¯/σtt¯jj are measured using data corresponding to an integrated luminosity of 2.3 fb−1collected in pp collisions at s=13 TeV with the CMS detector at the LHC. Events with two leptons (e or μ) and at least four reconstructed jets, including at least two identified as b quark jets, in the final state are selected. In the full phase space, the measured ratio is 0.022±0.003(stat)±0.006(syst), the cross section σtt¯bb¯ is 4.0±0.6(stat)±1.3(syst) pb and σtt¯jj is 184±6(stat)±33(syst) pb. The measurements are compared with the standard model expectations obtained from a POWHEG simulation at next-to-leading-order interfaced with PYTHIA.